2020
DOI: 10.1007/s00134-020-06061-y
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular overloading identified by critical care echocardiography is key in weaning-induced pulmonary edema

Abstract: To assess the role of left ventricular overload and cumulated fluid balance in the development weaninginduced pulmonary edema (WIPO). Methods: Ventilated patients in sinus rhythm with COPD and/or heart failure (ejection fraction ≤ 40%) were studied. Echocardiography was performed immediately before and during a 30-min spontaneous breathing trial (SBT) using a T-tube. Patients who failed were treated according to echocardiography results before undergoing a second SBT. Results: Twelve of 59 patients failed SBT,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 42 publications
(75 reference statements)
2
27
0
Order By: Relevance
“…Again, no significant difference was observed for the E ′ wave maximal velocity and E / E ′ ratio (Table 1 ). These data confirm those reported initially when dichotomizing patients according to passed or failed SBT [ 2 ].…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Again, no significant difference was observed for the E ′ wave maximal velocity and E / E ′ ratio (Table 1 ). These data confirm those reported initially when dichotomizing patients according to passed or failed SBT [ 2 ].…”
supporting
confidence: 91%
“…We read with interest the correspondence by Sanfilippo et al [ 1 ] who suggest performing further analysis for our recently reported study [ 2 ]. As per their thoughtful suggestion, we first redefined the two study groups as “weaning success” ( n = 43) when the patient could be extubated without reinstitution of ventilator support within 48 h after extubation, and as “weaning failure” ( n = 16) whenever one the following occurred: (i) failed spontaneous breathing trial (SBT) ( n = 12); (ii) reintubation and/or resumption of ventilator support within 48 h after extubation ( n = 3); or (iii) death in the 48 h after extubation ( n = 1) [ 3 ].…”
mentioning
confidence: 96%
“…We read with great interest the elegant study recently published by the group of Goudelin et al [ 1 ] where authors studied weaning from mechanical ventilation (MV) in a population with chronic-obstructive pulmonary disease (COPD) and/or heart failure with reduced ejection fraction (HFrEF). The authors confirmed that left ventricular (LV) overloading is a key aspect of weaning-induced pulmonary oedema (WiPO).…”
mentioning
confidence: 99%
“…In this interesting study published in the journal [ 1 ], the authors showed that 47 out of 59 patients successfully passed their first SBT, while 12 had failed. Noteworthy, four patients “passing the SBT” subsequently met the criteria of “extubation failure within 48 h”, but they were still analysed as “successful SBT”.…”
mentioning
confidence: 99%
See 1 more Smart Citation